Dietary phytochemical and metabolic disease prevention: Focus on plant proteins - Yang, Song-hong; Tao, Gabriel; Yang, Liu; Wu, Xiaohui; Liu, Jing-wen; Dagher, Fatima; Ou, Shi-yi; Song, Yuan; Huang, Jun-qing (Frontiers in Nutrition, 2023)
Plant-based functional foods have attracted increasing research interest to validate their use in preventing metabolic disease. Since it is increasingly recognized that inflammation, oxidative stress and circadian rhythm play vital roles in various metabolic diseases, including diabetes, obesity and nonalcoholic liver disease, plant proteins, protein hydrolysates and food extracts that intervene in these biological processes are promising dietary supplements to prevent metabolic diseases. Here, we reviewed the recent research on plant-based foods used for metabolic disease prevention and provided new perspectives regarding the current study gaps and future directions in this field.